The Challenger explosion - Adamson, Heather; Bascle, Brian (Mankato, MI : Capstone Press, 2006)
In graphic novel format, tells the story of Christa McAuliffe and the six other NASA astronauts who lost their lives in the Challenger space shuttle disaster on January 28, 1986.
9 - 12 years
Keywords: McAuliffe, Christa -- 1948-1986; Challenger (Spacecraft) -- Accidents; Space shuttles; Astronauts -- United States